Optically trapped Feshbach molecules of fermionic ^{161}Dy and ^{40}K - E. Soave; A. Canali; Zhu-Xiong Ye; M. Kreyer; E. Kirilov; R. Grimm (Physical Review Research, 2023)
We report on the preparation of a pure ultracold sample of bosonic DyK Feshbach molecules, composed of the fermionic isotopes ^{161}Dy and ^{40}K. By sweeping a magnetic field across a resonance located near 7.3 G, we generate up to 5000 molecules at a temperature of approximately 50 nK. To purify the sample from remaining atoms, we employ a Stern-Gerlach technique that relies on magnetic levitation of the molecules in a very weak optical dipole trap. With the trapped molecules we finally reach a high phase-space density of about 0.1. We investigate the magnetic field dependence of the molecular binding energy and the magnetic moment, refining our knowledge of the resonance parameters. We also demonstrate a peculiar anisotropic expansion effect observed when the molecules are released from the trap and expand freely in the magnetic levitation field. Furthermore, we identify an important lifetime limitation that is imposed by the 1064-nm infrared trap light itself and not by inelastic collisions. The light-induced decay rate is found to be proportional to the trap light intensity and the closed-channel fraction of the Feshbach molecule. These observations suggest a one-photon coupling to electronically excited states to limit the lifetime and point to the prospect of loss suppression by optimizing the wavelength of the trapping light. Our results offer crucial insights and experimental progress towards achieving quantum-degenerate samples of DyK molecules and novel superfluids based on mass-imbalanced fermion mixtures.